Comparison of the Rate and Level of Biodegradation of Leaf Waste by Lignocellulolytic Molds from Universitas Negeri Semarang Campus - Walandipa, Ghani; Mustikaningtyas, Dewi; Widiatningrum, Talitha; Dewi, Pramesti (Universitas Negeri Semarang, 2025)
Biodegradation is a physical decomposition of the substrate caused by the activity of microorganisms by producing products that have benefits for humans. Lignocellulose degrading fungi are microorganisms that play a role in the process of decomposing organic waste. The biodegradation rate of each type of lignocellulose degrading mold is different. The purpose of this research is to comprehensively analyze and compare the rate and level of biodegradation of leaf waste in lignocellulolytic molds isolated from the campus environment of Universitas Negeri Semarang, as well as to identify and evaluate the type of lignocellulolytic mold that shows the highest efficiency in the rate and level of biodegradation of leaf waste. The method used in this research is quantitative method, by measuring the mass ratio and pH of leaf waste media before inoculation and after inoculation. The results of this study are the rate of leaf waste biodegradation based on the ratio of leaf waste mass by Trichoderma koningiopsis mold isolate of 0.015 grams/day, while by Trichoderma erinaceum mold isolate of 0.002 grams/day. Then the rate of leaf waste biodegradation based on the pH change value of leaf waste by Trichoderma koningiopsis mold isolate is higher with a pH change value of 0.3 when compared to the Trichoderma erinaceum mold isolate with a pH change value of 0.1. The superior performance of Trichoderma koningiopsis highlights its potential application in optimizing organic waste decomposition systems and provides a scientific basis for selecting lignocellulolytic fungi in sustainable waste management programs.